Interdelivery intervals for a vaginal birth after delivery - Ismail, Hamizah; Nusee, Zalina; Mohd Rus, Razman (IIUM Press, 2017)
The aim of this study was to determine the successful rate of vaginal birth after caesarean (VBAC) in women with inter-delivery interval (IDI) below and above 19 months (≤ 19 months), apart from comparing the maternal morbidity and the fetal outcome between the two groups. This is a cross-sectional study that was conducted in the Obstetrics & Gynaecological Department Hospital Tengku Ampuan Afzan, Kuantan Pahang from June 2013 until June 2015.